Enhancing clinical evidence by proactively building quality into clinical trials. (August 2016) - Meeker-O'Connell, Ann; Glessner, Coleen; Behm, Mark; Mulinde, Jean; Roach, Nancy; Sweeney, Fergus; Tenaerts, Pamela; Landray, Martin J
Background: Stakeholders across the clinical trial enterprise have expressed concern that the current clinical trial enterprise is unsustainable. The cost and complexity of trials have continued to increase, threatening our ability to generate reliable evidence essential for making appropriate decisions concerning the benefits and harms associated with clinical interventions. Overcoming this inefficiency rests on improving protocol design, trial planning, and quality oversight. Methods: The Clinical Trials Transformation Initiative convened a project to evaluate methods to prospectively build quality into the scientific and operational design of clinical trials ("quality-by-design"), such that trials are feasible to conduct and important errors are prevented rather than remediated. A working group evaluated aspects of trial design and oversight and developed the Clinical Trials Transformation Initiative quality-by-design principles document, outlining a series of factors generally relevant to the reliability of trial conclusions and to patient safety. These principles were then applied and further refined during a series of hands-on workshops to evaluate their utility in facilitating proactive, cross-functional dialogue, and decision-making about trial design and planning. Following these workshops, independent qualitative interviews were conducted with 19 workshop attendees to explore the potential challenges for implementing a quality-by-design approach to clinical trials. The Clinical Trials Transformation Initiative project team subsequently developed recommendations and an online resource guide to support implementation of this approach. Conclusion: The Clinical Trials Transformation Initiative quality-by-design principles provide a framework for assuring that clinical trials adequately safeguard participants and provide reliable information on which to make decisions on the effects of treatments. The quality-by-design workshops highlighted the value of active discussions incorporating the different perspectives within and external to an organization (e.g. clinical investigators, research site staff, and trial participants) in improving trial design. Workshop participants also recognized the value of focusing oversight on those aspects of the trial where errors would have a major impact on participant safety and reliability of results. Applying the Clinical Trials Transformation Initiative quality-by-design recommendations and principles should enable organizations to prioritize the most critical determinants of a trial's quality, identify non-essential activities that can be eliminated to streamline trial conduct and oversight, and formulate appropriate plans to define, avoid, mitigate, monitor, and address important errors.